Comparison on chemical, structural, thermal, functional and antioxidant properties of polysaccharides and phenolics co-extracted from mangosteen (Garcinia mangostana Linn) peels by different eco-friendly hybrid technologies - Nhu Bich Ma; Nguyen Ngoc Thanh Tien; Linh Tran Khanh Vu; Nu Minh Nguyet Ton; Ngoc Lieu Le (Journal of Agriculture and Food Research)
This project aimed to compare the characteristics of the polysaccharides and phenolics simultaneously isolated from the peels of mangosteen using two hybrid methods: ultrasound-microwave (UMAE) and enzyme-ultrasound assisted extraction (EUAE). The polysaccharides extracted from mangosteen peels had dark brown to yellow color and rough surface with irregularly shaped particles, an accomplished purification of 92.5–94.8 %, medium degree of esterification (48–53 %), two molecular weights (0.12–2.42 × 105 Da and 11.66 to 13.24 × 105 Da), thermal profiles of two endothermic peaks and one exothermic peak, and monosaccharide profiles rich in arabinose, glucose, and galactose. However, UMAE polysaccharides possessed higher methoxyl content (6.4 %), anhydrouronic acid content (69 %), but lower solubility (69 %), equivalent weight (540 g/mol), total phenolic content (25.9 mg gallic acid equivalent (GAE)/g dry weight (DW)), anthocyanin content (37.5 mg cyanidin-3-glucoside (C3G)/100 g DW), and antioxidant activity (24.9 mg Trolox equivalent (TE)/g DW) than EUAE ones (1.22 %, 15 %, 91 %, 2300 g/mol, 42.1 mg GAE/g DW, 65.3 mg C3G/100 g DW, and 44.64 mg TE/g DW, respectively). Regarding the phenolics, both techniques produced the products with quite similar antioxidant properties in terms of total phenolics (222.7–230 mg GAE/g DW), total flavonoids (62–78 mg rutin equivalent/g DW), anthocyanin (95–108 mg C3G/100 g DW). However, EUAE phenolic extract exhibited higher α-mangostin, and γ-mangostin content (approximately 50 % higher) than UMAE one, leading to its higher antioxidant activity. In conclusion, both extraction methods provide eco-friendly ways to obtain valuable products from mangosteen peels with potential health benefits and diverse applications.